2010
DOI: 10.1186/1746-6148-6-19
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and gastrointestinal immune systems of healthy cattle raised outdoors at pasture or indoors on a concentrate-based ration

Abstract: BackgroundDespite an increasing preference of consumers for beef produced from more extensive pasture-based production systems and potential human health benefits from the consumption of such beef, data regarding the health status of animals raised on pasture are limited. The objective of this study was to characterise specific aspects of the bovine peripheral and the gastrointestinal muscosal immune systems of cattle raised on an outdoor pasture system in comparison to animals raised on a conventional intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Several factors may affect the population of leukocytes in the peripheral blood of cattle, including age (Guzman et al, 2012), sex or reproductive stage (Oliveira and Hansen, 2008), and environment (Lejeune et al, 2010). In this study, these factors should not have played any significant role since all cattle studied were prepubertal, within the same age range, and they were raised under standardized, conventional conditions for these breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may affect the population of leukocytes in the peripheral blood of cattle, including age (Guzman et al, 2012), sex or reproductive stage (Oliveira and Hansen, 2008), and environment (Lejeune et al, 2010). In this study, these factors should not have played any significant role since all cattle studied were prepubertal, within the same age range, and they were raised under standardized, conventional conditions for these breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Newborn calves fed colostrum for 14 days postpartum had 108 less days per treatment group of gastrointestinal distress, as monitored by diarrhea, than calves fed milk replacer (Berge et al , 2009). Furthermore, calves grazing pastures had significantly different immunological profiles, exemplified by lower IFN-γ production from ConA stimulated leukocytes and significantly different cytokine profiles from small intestine tissue, when compared to indoor-housed heifers fed a grain-based diet (Lejeune et al , 2010). Furthermore, when Callaway et al (2010) used bacterial tag-encoded FLX amplicon pyrosequencing to define diversity in rumen and faeces, they observed that as dietary supplementation with dried distiller grains increased there was a decreased Firmicutes : Bacteroidetes ratio within ruminal fluid, an increased proportion of Acinetobacter in feces and that pH decreased on higher grain diets.…”
Section: Microbial Colonization Of the Git In Newborn Calvesmentioning
confidence: 99%
“…O'Brien et al (1999) demonstrated that milk Cu and I were found to be higher during winter periods, whereas no clear trend in the changes of Mn, Mo, Zn, Co, Cr, and Fe levels was observed (O'Brien et al 1999). Correspondingly, administration of a concentrate-based ration was associated with higher blood I level (Lejeune et al 2010). In addition, it has been demonstrated that the intake of Co is also associated with the administration of concentrate feeds (Orjales et al 2018).…”
Section: Discussionmentioning
confidence: 98%